EVALUATION OF PHOTORECEPTORS, RETINAL CAPILLARY PLEXUSES, AND CHORIOCAPILLARIS IN PATIENTS WITH BIRDSHOT CHORIORETINOPATHY. Issue 5 (May 2020) - Forte, Raimondo; Saleh, Maher; Aptel, Florent; Chiquet, Christophe
Abstract : Purpose: To assess the status of the cone photoreceptors using adaptive optics flood illumination ophthalmoscopy in patients with birdshot chorioretinopathy and to study their relationship with optical coherence tomography (OCT) angiography. Methods: Seventeen patients with birdshot chorioretinopathy were studied using standard automated perimetry, color vision testing, fluorescein angiography, indocyanine green angiography, spectral domain OCT, enhanced depth imaging OCT, and adaptive optics flood illumination ophthalmoscopy (rtx1, Imagine Eyes, Orsay, France) in a 90 × 90- μ m area at 1.5° temporal of the fovea and OCT angiography (Spectralis OCT2, Heidelberg Engineering, Heidelberg, Germany). For adaptive optics flood illumination ophthalmoscopy, spectral domain OCT, and OCT angiography, a control group of 12 healthy patients (12 eyes) matched for age, sex, and refractive error was included. Results: After excluding low-quality adaptive optics flood illumination ophthalmoscopy images, 12 eyes (12 patients, 7 women, mean age 53.5 ± 10.8 years) were analyzed. Best-corrected visual acuity was 0.01 ± 0.03 LogMAR (20/25 Snellen equivalent), and foveal threshold at standard automated perimetry was 35.2 ± 3.0. Cone density at 1.5° of the fovea in the birdshot chorioretinopathy group (11, 435.25 ± 4, 342.9 cells/mm 2 ) was significantly smaller than in the control group (24, 594.04 ± 4, 764.3 cells/mm 2, P < 0.001). In the same area, birdshot chorioretinopathy eyes showed disruption of the ellipsoid/interdigitation zone and vascular abnormalities, such as capillary loops (58.3%), increased superficial intercapillary spaces (75%), increased deep intercapillary spaces (58.3%), capillary dilations (58.3%), telangiectatic vessels (66.6%), and absence of choriocapillary flow (58%). Cone density at 1.5° was associated with duration of the disease (Spearman's rho −0.8, P = 0.01), although it was not associated with OCT angiography abnormalities in the same area. Conclusion: Birdshot chorioretinopathy can result in a reduction in cone density and development of macular vascular abnormalities even in the presence of preserved visual function. Abstract : In eyes with birdshot chorioretinopathy and preserved visual function, adaptive optics and optical coherence tomography angiography detected a reduction in cone density and the presence of macular vascular abnormalities.